Hambatan Sosial Budaya dalam Pelaporan Kekerasan Seksual di Kabupaten Pohuwato - Rahmat Ladiku; Dewinta Rizky R. Hatu; Sahrain Bumulo; Sabrina Nadia (Program Studi Sosiologi, Fakultas Ilmu Sosial Universitas Negeri Gorontalo, 2026)
Sexual violence is often underreported because reporting decisions are shaped not only by the availability of formal services but also by social relations, stigma, trust, and local norms. This article analyzes socio-cultural barriers that influence the reporting of sexual violence in Pohuwato Regency, with empirical attention to Marisa and Buntulia Districts. The study uses a descriptive qualitative approach based on field data collected through semi-structured interviews, non-participant observation, and documentation. Informants were selected purposively from the local women and child protection service, district government, and community elements relevant to the reporting and handling process. The data were reduced, organized thematically, and interpreted through an interactive qualitative analysis. The findings identify four interrelated barriers. First, limited public understanding of the role and reporting mechanism of UPTD PPA weakens institutional trust. Second, fear of stigma and social consequences makes prospective reporters delay or reconsider formal reporting. Third, the social standing and familiarity of perpetrators may produce disbelief toward victims and strengthen social pressure. Fourth, norms that frame sexual violence as a private family matter encourage informal settlement and may interrupt formal reporting. These mechanisms help explain why official case figures cannot automatically be treated as the full magnitude of sexual violence. Strengthening reporting therefore requires not only accessible institutions but also continuous community education, trusted local protection networks, confidential victim-centered services, and interventions that challenge social pressure against victims.